Effects of Participatory Strategic Development Process Among Personnel Under Nakhon Pathom Provincial Public Health Office - กตัญญูทิตา สุภัทร (Journal of Health Science of Thailand, 2025)
Abstract Objective: To study the effects of participatory strategic development processes among personnel under the Nakhon Pathom Provincial Public Health Office. Methodology: This study employed a research and development approach, conducted from March to September 2024, using mixed methods combining both quantitative and qualitative approaches. The study population comprised 268 personnel from all affiliated units under the Nakhon Pathom Provincial Public Health Office, including the Provincial Health Office, Regional Hospital, 8 Community Hospitals, 7 District Health Offices, and 98 Sub-district Health Promoting Hospitals. Data were collected through questionnaires, in-depth interviews, and operational performance reports with Key Performance Indicators (KPI). Data analysis employed both descriptive and inferential statistics, including frequency distribution, percentage, standard deviation, F-test, and paired t-test. Results: The participatory strategic development of Nakhon Pathom Provincial Health Services demonstrated significant improvements across multiple dimensions. In the pre-implementation phase, the overall level of understanding in strategic implementation was high (Mean = 3.44, S.D. = 0.43), with strategic issue identification scoring highest while capacity analysis scored lowest. The overall participation level was moderate (Mean = 3.37, S.D. = 0.48). Post-development analysis revealed statistically significant changes at the .05 level (p-value = .000), with the level of strategic implementation understanding increasing to the highest level (Mean = 4.50, S.D. = 0.37) and participation levels also rising to the highest level (Mean = 4.60, S.D. = 0.46) across all aspects. The development resulted in a model comprising three main components: 1) provincial-wide understanding of strategic implementation, 2) participatory engagement in implementation, and 3) strategic management. This led to the creation of two significant innovations: the Nakhonchaisri Model for health resource management system development in Nakhonchaisri District, and the KBD Model for shared resource management among Kamphaeng Saen, Bang Len, and Don Tum Hospitals. Conclusion: The statistically significant changes in both understanding and participation in strategic implementation led to the development of two important innovations: the Nakhonchaisri Model and the KBD Model for health resource management. Keywords: Strategic Development Process, Participation, Health System